ENCAPSULATION OF MICROPROPAGATED BUDS OF SIX WOODY SPECIES. - PICCIONI, EMANUELE; ALVARO STANDARDI
Regrowth after encapsulation in a sodium alginate matrix of micropropagated buds from six different in vitro proliferated woody species was evaluated. Actinidia deliciosa Liang & Ferguson (kiwifruit), Betula pendula Roth (birch), Crataegus oxyacantha L. (hawthorn), Malus spp. (apple), Rubus spp. (blackberry) and Rubus idaeus L. (raspberry) propagated in vitro were used as bud sources. Encapsulation with sodium alginate and subsequent regrowth on nutrient rich medium was compared to encapsulation with nutrient-enriched alginate capsules followed by regrowth on nutrientless medium. Apical and sub-apical buds of Malus (rootstock `M. 27` and cultivar Starkspur Red`) were also compared for encapsulation and regrowth ability. Ah species showed a regrowth after encapsulation, but only if cultured on enriched media. `M.27` apical and sub-apical buds showed different regrowth ability alter encapsulation with sodium alginate. Applicability of encapsulation of single micropropagated tree buds is dis
Keywords: ORNAMENTALES; BIOTECNOLOGIA; FRAMBUESA; ARBUSTOS ORNAMENTALES; SEMILLAS; ARBOLES MADERABLES; CULTIVO IN VITRO 2. CRATEGUS OXYACANTHA 3. MALUS RUBUS 4. IDAEUS 5. ENCAPSULACION 6. YEMA 7. MERISTEMAS 8. APICALES 9. FRUTAS TROPICALES; ANVIDAD DELICIOSA; BETULA PENDULA; Artículos de revista